2012
DOI: 10.1161/circinterventions.112.972869
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin Versus Heparin Plus a Glycoprotein IIb/IIIa Inhibitor in Patients With Non–ST-Segment Elevation Myocardial Infarction Undergoing Percutaneous Coronary Intervention After Clopidogrel Pretreatment

Abstract: N on-ST-segment elevation acute coronary syndromes (ACS) account for approximately two thirds of patients with ACS.1 Patients with biomarker-positive non-ST-segment elevation myocardial infarction (NSTEMI) represent a highrisk group that differs from biomarker-negative ACS patients with regard to benefit from invasive treatment 2 or type of antithrombotic therapy 3 and prognosis. 4 An early invasive strategy of coronary angiography and revascularization when appropriate improved the outcomes of patients with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Compared with our analysis, only the post hoc results of the ACUITY trial showed a decrease in major bleeding with bivalirudin use in diabetes patients undergoing PCI, whereas the post hoc results of both HORIZONS‐AMI and REPLACE‐2 as well as the NAPLES trial showed no differences in major bleeding events between these two treatment arms. In a patient‐level pooled data from the ACUITY and ISAR‐REACT 4 trials, major bleeding was decreased with bivalirudin use in NSTEMI patients with diabetes who were pretreated with clopidogrel . Similar to our analysis, minor bleeding was lower with bivalirudin use in all studies that reported it.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Compared with our analysis, only the post hoc results of the ACUITY trial showed a decrease in major bleeding with bivalirudin use in diabetes patients undergoing PCI, whereas the post hoc results of both HORIZONS‐AMI and REPLACE‐2 as well as the NAPLES trial showed no differences in major bleeding events between these two treatment arms. In a patient‐level pooled data from the ACUITY and ISAR‐REACT 4 trials, major bleeding was decreased with bivalirudin use in NSTEMI patients with diabetes who were pretreated with clopidogrel . Similar to our analysis, minor bleeding was lower with bivalirudin use in all studies that reported it.…”
Section: Discussionsupporting
confidence: 82%
“…The higher risk of complications faced by diabetes patients who develop ACS and undergo PCI highlights the importance of evaluating such a strategy in this specific patient population. Moreover, outcomes in diabetes patients in previously published meta‐analyses and patient‐level pooled data of randomized trials comparing bivalirudin with heparin and GPI in PCI have been limited . Given the scarcity of data published on this topic, we sought to perform a pooled analysis to evaluate the use of bivalirudin compared with heparin and GPI in diabetes patients undergoing PCI and report both 30‐day and 1‐year clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Bivalirudin has consistently shown to reduce the bleeding risk of patients with coronary artery disease undergoing PCI compared with heparin and glycoprotein IIb/IIIa inhibitors, particularly those presenting with an ACS. [97][98][99] A recent meta-analysis has confirmed the safety benefit of bivalirudin over unfractionated heparin alone. 100 However, there are no studies exploring whether such benefit is enhanced, similar, or blunted in patients who are orally anticoagulated.…”
Section: Intraprocedural Anticoagulationmentioning
confidence: 98%
“…The direct-acting thrombin inhibitor bivalirudin is recommended as an alternative to UFH (plus GPIIb/IIIa inhibitors) during PCI (Class I, LOE A). Based on the results of clinical trials comparing these two agents and related meta-analysis (75)(76)(77), bivalirudin increased the risk of ischaemic events, while it decreased the risk of bleeding. However, available data is conflicting and further studies are urgently needed to compare UFH versus bivalirudin in a contemporary setting that includes a preferred radial access for PCI and that excludes the use of GPIIb/IIIa inhibitors in any of the study arms.…”
Section: The Presentmentioning
confidence: 99%